Infliximab 치료로 호전된 재발다발연골염 1예 - 이상진; Sang Jin Lee; 양지애; Ji Ae Yang; 박준원; Jun Won Park; 고동진; Dong Jin Ko; 권현미; Hyun Mi Kwon; 문진영; Jin Young Moon; et al. (Journal of rheumatic diseases, 2014)
저자들은 국내에서 처음으로 재발다발연골염에 생물학적 제제 사용으로 호전된 바 있는 1예를 경험하였기에 문헌고찰과 함께 보고하는 바이다. Relapsing polychondritis is an episodic, systemic inflammation of the cartilage with unknown autoimmune etiology. It leads to the destruction of cartilaginous structures of the ear, eye, nose, respiratory tract, joints, skin, and heart valve, and its presented symptoms are diverse. It can be improved mainly by corticosteroid or immunosuppressive agents. Recently, the use of biologic agents (TNF inhibitors, rituximab, tocilizumab et al) was reported from abroad. However, there is no reported case of relapsing polychondritis, which is treated by biologic agents in Korea. We report this first case of refractory relapsing polychondritis, which was improved with a treatment of Infliximab.